Temporary trend of suicide in the state of Espírito Santo, 2007 to 2016 (Brazilian Journal of Health Research, 2022)
Introduction: Suicide is a complex and multicausal phenomenon that occurs in all regions of the world and defies modern societies because it is an avoidable death. Objectives: To analyze the temporal trend of suicide mortality in the state of ES from 2007 to 2016. Methods: Time-series ecological study whose population comprised the deaths of 10 years or more by suicide in the health regions of ES, from 2007 to 2016, based on the Mortality Information System. Descriptive statistics were performed and polynomial regression models were estimated for suicide trend analysis. Results: A total of 1,630 suicide deaths were reported in Espírito Santo in the analyzed period. The model that represented the trend of death by suicide was second order (p
Keywords: Suicide; Mortality; Intention; Public Health